Pengembangan Model Lingkungan Pendidikan Berkelanjutan melalui Evidence-Based Design di Sekolah Alam Bandung - Yudhistira Kusuma; Ana Ramdani Sari; Try Ramadhan; Trias Megayanti; Dian Fitria; Rr. Tjahyani Busono (Universitas Sebelas Maret Surakarta, 2026)
Development of a Sustainable Education Environment Model through Evidence-Based Design at Sekolah Alam BandungEnvironmental education aimed at fostering pro-environmental behavior has become an urgent necessity. The education (school) is seen as an effective environment to encourage such behavior because there are pedagogical elements in its architecture that can educate users about environmental issues. This study examines the elements that play a role in environmental education at Bandung Nature School in a sustainable educational environmental design principle through an evidence-based design framework. This study employed a qualitative approach using a case study method. The results of the study provide six principles of a sustainable educational environment model based on evidence from the Sekolah Alam Bandung: selection of a specific location, massing and placement of buildings, structures and materials, integration of the natural environment, active settings as learning platform, and flexible learning spaces.